Leveraging Blockchain Technology for Auditable and Privacy-Friendly Data Exchange in Teleradiology Networks - Alhathiq, Abdulelah Hassan; Rayyani, Abdullah Ahmed; Khawaji, Mohammed Nasser; Mabuj , Jebril Mohammed; Radwan, Akram Hadi; Aloraini, Lama Nasser; Alorf, Amjad Rashed; Alarifi, Heba Saad; Alhuwaimel, Sami Abdulaziz; Alrashed, Lina Abdulaziz (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Teleradiology, distant transmission and interpretation of medical images, has revolutionized healthcare by increasing diagnostic availability, particularly in underserved communities. However, its digital platform is vulnerable to threats of data breaches and invasions of privacy, with healthcare data breaches costing 2.1 million per breach in 2015. <span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to address the history of safe data transmission and privacy protection in teleradiology, particularly through technological advancements, regulatory settings, ethical considerations, and challenges. <span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A systematic review was conducted, and articles were fetched from PubMed, Scopus, IEEE, and ACM Digital Library. Keywords used were "teleradiology," "secure data exchange," and "privacy." Two tables of principal technologies and regulatory frameworks are given. <span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Advances in encryption, blockchain, AI, and IoMT provide security, but scalability, computational complexity, and regulation gaps pose obstacles. Ethical issues, including patient autonomy and trust, remain paramount. Case studies demonstrate that blockchain and AI are reducing tampering and data breaches. <span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 10pt; font-family: ’Times New Roman’, serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Security in teleradiology requires hybrid models, global regulatory harmonization, and patient-centric privacy frameworks to serve the requirements of access and protection. Scalability and equity must be tackled in future studies.